USO DE ESTREPTOMICINA NA ELIMINAÇÃO DA LEPTOSPIRÚRIA EM TOUROS (BOS TAURUS INDICUS) NATURALMENTE INFECTADOS PELO SOROVAR HARDJO - Girio, T. M. S. [UNESP] (2022)
The objective of this work was evaluated different marks of streptomycin for the treatment of bovine leptospirosis, in an only one dose of 25 mg for kg of corporeal weight. Thirty serologically reactive bulls for Leptospira interrogans serovar Hardjo were utilized. The bulls had a minimum antibody titer of 800 and were positive in the isolation from urine samples. The animals had been separated in 2 groups according with the streptomycin mark used in the treatment, group 1: streptomycin A and group 2: streptomycin B. The bovine controls had received any application from streptomycin. Samples of blood and urine of treated and controls bulls were collected in days -1, 0, 1, 2, 3, 5, 10, 15 and 25; considering the day of the treatment as day 0. A research for the detection of leptospira genetic material was realized in the urine of all bulls by PCR. It was observed that the streptomycin A ended leptospiruria in 24h after of the treatment. In the group of bulls treated with the streptomycin B, the end of leptospiruria was evidenced in 48h and 72h, after the treatment. In both treated groups, the serological reply presented a variation in the fall of antibodies titers, and streptomycin A was better in comparative performance with geométric means of the antibodies titers of the group that received streptomycin B, although by the Tukey Test the difference was no significant (P > 0.05). In the bovine controls the leptospiruria was intermittent and the average of the antibody titers of the treated bovines was lower than the average of the bovine controls, during all the experiments. The difference in the effect of different brands of streptomycin is possibly due to the quality of the substances produced in the laboratories.